ANALYSIS IN THE LEGAL DYNAMICS OF COENANT VIA INTERNET IN INDONESIA - Amrin, Amrin; Hidayat, Arsad; Supriyanto, Supriyanto (Journal of Religious Policy, 2023)
This research aims to analyze the juridical, philosophical and sociological aspects of the legal dynamics of coenant via the internet in Indonesia. This research uses a qualitative type with library research. Meanwhile, the research approach used is descriptive, juridical, philosophical and sociological analysis. The data analysis used is qualitative data analysis. The results of the research show that there are differences of opinion among Ulama regarding coenant via Internet which are based on differences in methods of understanding the texts of the Koran and hadith regarding marriage, and are related to the development of science and technology. In Indonesia, from a juridical-philosophical perspective, the practice of coenant via the Internet is recognized as legal because all legal facilities and requirements have been fulfilled. However, from a sociological perspective, most Muslim communities in Indonesia still strongly believe marriage is a sacred moment. Therefore, even though the practice of coenant via teleconference is legally recognized, it is still difficult for society to accept it widely because the traditional paradigm related to the sacredness of marriage still dominates. As a legal state, strategic steps are needed to establish a clear and comprehensive legal status regarding the legality of carrying out marriages via the Internet. There is an excellent possibility in the future with advances in science and technology, it is not without reason that the Indonesian Muslim community uses the internet as an instrument in carrying out coenant.